PSYCHOLOGICAL CONFIDENCE AND ORGANIZATIONAL COMMITMENT IN SELECTED TELECOMMUNICATION ORGANISATIONS IN NIGERIA - B. M. Nwibere; G.O. Worlu (Scholars Digest Publishing, 2023)
Confidence and organisational commitment. The sample comprised 280 managerial and non-managerial employees from four major telecommunication companies in Nigeria. A quasi-experimental research design was employed as it is deemed most suitable for the field of administrative sciences. Data collection involved primary and secondary sources. The Spearman rank correlation coefficient, utilising the Statistical Package for the Social Sciences (SPSS) version 25, was utilised for data analysis. The findings revealed a positive and significant relationship between psychological confidence (operationalised as self-efficacy and self-esteem) and organisational commitment. Specifically, self-efficacy and self-esteem were found to positively and significantly influence various dimensions of organisational commitment, including affective, normative, and continuance commitment. In light of these findings, we conclude that psychological confidence enhances organisational commitment within the telecommunication industry. Consequently, it is recommended that managers in the Nigerian telecommunication sector effectively cultivate their employees' psychological confidence (self-esteem and self-efficacy) to foster a more significant commitment to the organisation. Additional practical implications for managing employees’ psychological confidence and organisational commitment in the workplace are also discussed.